Factors Affecting Green Purchase Behavior of Cosmetic Products Among Millennial Consumers in Indonesia - Dwi Dini Pratiwi (UIN Raden Mas Said Surakarta, 2020)
The industry development of green cosmetic products in Indonesia encourages the prominence of studies related to green purchase behavior. This study aimed to determine the factors encouraging consumers to make green purchase intention which then lead to green purchase behavior for cosmetic products among millennials in Indonesia. Millennials were chosen because nowadays they dominate the population in Indonesia and are the largest users of cosmetic products, so they are considered influential in the cosmetics industry. Besides, millennials are also considered to have the most awareness of environmental issues. This research was conducted by collecting primary data through the distribution of online surveys to 100 people who had purchased green cosmetic products and were millennials seen from their age. Validity and reliability tests were carried out to ensure that the data was suitable for use, followed by the design of the structural model to test the hypothesis. Based on the results of this study, the factor of environmental concern had a significant positive effect on green purchase intention, while the factor of personal norms had no positive effect on green purchase intention. Green purchase intention also had a positive effect on green purchase behavior. The findings in this study can be used as a reference for companies, particularly marketers, to be able to consider environmental aspects in their business processes so that they can increase competitive advantage and as an effort to overcome the issues on environmental sustainability that are being faced at the moment.